Energy flow models for underwater radiation noise prediction in medium-to-high-frequency ranges. (May 2016) - Kwon, Hyun-Wung; Hong, Suk-Yoon; Song, Jee-Hun
Energy flow analysis is studied as a promising tool for the noise and vibration analysis of system structures in medium-to-high-frequency ranges. The energy flow finite element method, combining energy flow analysis with the finite element method, is efficient for the vibration analysis of a built-up structure, and the energy flow boundary element method, combining energy flow analysis with the boundary element method, is useful for predicting the noise level of a vibrating complex structure. In this article, the energy flow finite element/energy flow boundary element method and semi-coupling relationships are used to investigate the vibration and radiation noise of a reinforced cylindrical structure in water. Energy flow finite element method is employed to analyze the vibrational responses of the reinforced cylindrical structure, considering fluid loading effects, and energy flow boundary element method is applied to analyze the underwater radiation noise. Therefore, the energy flow coupling relationship of structure-to-acoustic space is used to link the energy flow finite element/energy flow boundary element methods together. The vibrational energy of the structure is treated as an acoustic intensity boundary condition of energy flow boundary element method to calculate underwater radiation noise. Numerical simulations are presented and the results are compared with experimental measurements for the reinforced cylindrical structure in water.